THU0677 Pneumococcal antibody protection in rheumatological patients receiving bdmard therapy – a cross-sectional study. (12th June 2018) - Rasmussen, S.; Fuursted, K.; Nielsen, K.; Parks, N.; Sørensen, M.; Leutscher, P.; Rasmussen, C.
Abstract : Background: Severe pneumococcal infections contribute to increased mortality in patients with rheumatic diseases, and is preventable by vaccination against Streptococcus pneumoniae . EULAR recommends that pneumococcal vaccination should be strongly considered in patients with rheumatic diseases, however, need and timing of revaccination for this patient group remains unknown 1 . Since 2009, rheumatological patients from our department have been vaccinated against S. pneumoniae prior to initiation of bDMARD therapy, by use of the 23-valent pneumococcal polysaccharide vaccine (PPV23). To our knowledge, we are the only centre in Denmark to vaccinate these patients routinely. Objectives: The aim of the study was to determine the prevalence of rheumatological patients receiving bDMARD therapy with a protective level of antibodies against S. pneumoniae, and to identify possible factors of relevance affecting antibody production. Methods: Antibodies against 12 pneumoccocal serotypes were measured in the period of June to December 2017 in patients receiving bDMARD therapy initiated before March 1st 2017. A geometric mean level of all serotypes above 1 µg/ml was considered a protective antibody level. The patients had been diagnosed with rheumatoid arthritis, spondyloarthritis, psoriatic arthritis or juvenile idiopathic arthritis. The study group consisted of both vaccinated and unvaccinated individuals, where unvaccinated individuals initiated bDMARD therapy before vaccination occurred routinely. Differences in protection between vaccinated and unvaccinated patients were evaluated using the χ 2 test. We included the following variables in a logistic regression model, to analyse factors of possible significance to the protective level of antibodies: age, sex, diagnosis, methotrexate (MTX) and/or prednisolone treatment at time of vaccination, and years since vaccination. Results: A total of 319 patients were included in the study: 186 (58%) vaccinated and 133 (42%) unvaccinated patients. Among the vaccinated patients, 30% had a protective antibody level versus 0% of the unvaccinated patients (p<0.0001). Logistic regression analysis showed that a significantly smaller proportion of patients treated with MTX at time of vaccination had a protective antibody level compared with patients not treated with MTX (p=0.03; odds ratio: 2.3; 95% CI [1.1;4.7]). The same applied for advanced age at time of vaccination (p=0.04), whereas years since vaccination did not decrease antibody protection significantly (p=0.12). Conclusions: Only one third of PPV23 vaccinated rheumatological patients treated with bDMARD were observed with a GML of pneumococcal antibodies above 1 µg/ml. This suggests that a majority of these patients are not protected adequately against pneumococcal disease in spite of vaccination. MTX treatment at time of vaccination and advanced age were both independently associated with lack of protective antibody level. Reference: [1] van Assen S, Agmon-Levin N, Elkayam O, et al. EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis2011;70(3):414–422. Disclosure of Interest: None declared